The Resilience of Islamic Education Amid Political Fragmentation: A Historical Study of the Reign of Ali ibn Abi Talib - Gustina Gustina; Azmul Zul Fazli; Erbi Zaitun Arrohman; Maya Salwa Nasution; Yanti Yanti (Kutubkhanah, 2026)
This study aims to examine the influence of political conditions on Islamic education during the reign of Ali ibn Abi Thalib. The research employs a descriptive qualitative method with a library research approach. Data were collected from relevant books and journals. The data analysis involved reading and interpreting sources in line with the research objectives, followed by presenting the findings descriptively to enhance reader comprehension. The study addresses the issue in accordance with the research title. The unstable political climate shifted the government's focus away from developing formal educational institutions; however, it simultaneously heightened the urgency of advancing linguistics and interpretation as a response to the social crisis.